Boyden chamber - Falasca, Marco; Raimondi, C.; Maffucci, T. (2011)
The Boyden chamber, initially designed to study leukocyte chemotaxis, has become one of the most used tools to assess cell motility and invasion. The classical Boyden chamber consists of two compartments separated by a membrane representing a physical barrier that cells can overcome only by active migration. Since its initial introduction, a number of different Boyden chamber devices have been developed. The Boyden chamber can be adapted to study tumour cells' invasive properties by coating the membrane with different extracellular matrix proteins. The method described in this chapter is intended specifically for measuring the migration or invasion of human endothelial and cancer cells.